Deserto verde, imprensa marrom: o protagonismo político das mulheres nas páginas dos jornais - Mano, Maíra Kubík Taveira (2010)
This dissertation supports the hypothesis that the mainstream media covers with prejudice direct political actions led by women member of the dominated classes. There is a double prejudice: of gender and social class. To corroborate this hypothesis, we analyzed the reports in the newspapers Folha de S. Paulo and O Estado de S. Paulo during the protests of the International Women's Day between 1985 and 2006, with special attention the last one, where 2.000 women from Via Campesina occupied an area of Aracruz Celulose in Barra do Ribeiro (RS, Brazil). The publications were considered private apparatus of hegemony within the boundaries of Antonio Gramsci s theory